2019
DOI: 10.1029/2018gc007944
|View full text |Cite
|
Sign up to set email alerts
|

New Magnetic Constraints on Early‐Middle Miocene Uplift of the Liupan Shan, Northeastern Margin of the Tibetan Plateau

Abstract: New constraints on the uplift history of the Liupan Shan can improve our understanding of the tectonic consequences of the collision of the Indian and Asian plates, including the timing of the uplift of the Tibetan Plateau. Here we present a detailed magnetostratigraphy for the Kaimengou section near the piedmont of the Liupan Shan, which reveals that it spans the interval from 19.8 to 12.8 Myr. Together with the results of measurements of the anisotropy of magnetic susceptibility, rock magnetic measurements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…AMS is demonstrated to be efficient in investigating subtle tectonics-related fabrics in weakly deformed or undeformed clay-rich sedimentary sequences undergoing incipient tectonic deformation (Gilder et al, 2001;He et al, 2021;B. Li et al, 2020;Li et al, 2021;Lu et al, 2014;Nie et al, 2020;Parés, 2015;Parés et al, 1999;Soto et al, 2009;Su et al, 2016;Weil & Yonkee, 2012;Wu et al, 2019;. The comparison between AMS and paleostress data validates the reliability of AMS ellipsoids as paleostress indicator in compressional settings (e.g., Soto et al, 2009).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…AMS is demonstrated to be efficient in investigating subtle tectonics-related fabrics in weakly deformed or undeformed clay-rich sedimentary sequences undergoing incipient tectonic deformation (Gilder et al, 2001;He et al, 2021;B. Li et al, 2020;Li et al, 2021;Lu et al, 2014;Nie et al, 2020;Parés, 2015;Parés et al, 1999;Soto et al, 2009;Su et al, 2016;Weil & Yonkee, 2012;Wu et al, 2019;. The comparison between AMS and paleostress data validates the reliability of AMS ellipsoids as paleostress indicator in compressional settings (e.g., Soto et al, 2009).…”
mentioning
confidence: 60%
“…The AMS fabrics produce kinematic data to be compared to mesostructures such as folds and faults in northern Tibet (Gilder et al., 2001; He et al., 2021; B. Li et al., 2020; Li et al., 2021; Lu et al., 2014; Nie et al., 2020; Su et al., 2016; Wu et al., 2019; Yu, Huang, et al., 2014). These studies have shown that the orientation of the AMS ellipsoid is in most cases related to the local stress field.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise uplift mechanism is debated, the following coexisting end-member models have been proposed: (1) oblique subduction of surface materials (Tapponnier et al 2001); (2) lower crustal flow (Royden et al 1997); and (3) migration of mantle materials (England and Houseman 1989). These models are supported by evidence from seismological (Shen et al 2017), thermochronological (Wang et al 2011), magnetic (Wu et al 2019), and gravity analyses (Wang et al 2014). Uplift mechanisms can be studied using the gravity admittance method, which can calculate the initial loading ratio to reveal the loading source in the lithosphere (McKenzie 2003).…”
Section: Introductionmentioning
confidence: 99%